Protic ionic liquids as constituent of aqueous two-phase system based on acetonitrile: Synthesis, phase diagrams and genipin pre-purification - Alves Camêlo, Lídia Cristina; de Souza Dias Santos, Gabriela; Lucena de Souza, Ranyere; Faria Soares, Cleide Mara; Brandão Pereira, Jorge Fernando [UNESP]; Lima, Álvaro Silva (Elsevier, 2020)
The aim of this study was to evaluate the formation of aqueous two-phase systems (ATPS) based on different protic ionic liquids (PIL), synthesized using amines, and organic or inorganic acid, and acetonitrile (ACN). The ATPSs are used to pre-purify genipin from genipap (Genipa americana L.). All PILs (purity above 98%) were able to form ATPSs with ACN, the size of the biphasic region being directly dependent on salting-out aptitude of PIL anions and relative hydrophilicity of the corresponding cations. The highest solid–liquid extraction of genipin from genipap was achieved by using aqueous ACN solution at 75% (16.79 ± 0.06 mg g−1 dry raw material) as extractant. After the extraction stage, the ATPS was used as an integrated platform to pre-purify the genipin present in the extract. Three different overall mixture point compositions were tested, and those formed by [MEA][H2Cit] (25 wt%) + ACN (45 wt%) + water (30 wt%) at 298.15 ± 1.00 K and 0.10 ± 0.01 MPa showed the highest selectivity (S = 4.202 ± 0.009) and recovery of genipin in top phase (RTG = 56.74 ± 0.04%), and the purification factor in top phase was 5.9 fold.
Keywords: Extraction; Genipin; Integrated process; Phase equilibria; Protic ionic liquid